Methyl salicylate, a grape and wine chemical marker and sensory contributor in wines elaborated from grapes affected or not by cryptogamic diseases. (30th October 2021) - Poitou, Xavier; Redon, Pascaline; Pons, Alexandre; Bruez, Emilie; Delière, Laurent; Marchal, Axel; Cholet, Céline; Geny-Denis, Laurence; Darriet, Philippe
Highligths: MeSA can be assayed in wines at concentrations over its olfactory detection threshold. MeSA is extracted during alcoholic fermentation from V.vinifera grape skins and stems. MeSA in wines can be related to grapevine alteration level by several pathogens. Abstract: Methyl salicylate (MeSA) is a plant metabolite that induces plant defence resistance and an odorous volatile compound presenting green nuances. This volatile compound was shown to be present in wine samples, sometimes at concentrations above its olfactory detection threshold. MeSA is localized in grapes, particularly in the skins and stems, and is extracted during red wine vinification. It was detected at the highest concentrations in wines of several grape varieties, made from grapes affected by cryptogamic diseases, namely downy mildew caused by Plasmopara viticola, and black rot caused by Guignardia bidwellii. It has also been detected in wines from vines affected by Esca, a Grapevine Trunk Disease. MeSA can also be considered to be a chemical marker in grapes and wine indicative of the level of development of several vine cryptogamic diseases.